Assessment of material resource usage in Inuit skin clothing - Schmidt, Anne Lisbeth; Fortuna, Roberto; Petersen, Anette Hjelm; Jensen, Klaus Støttrup; Jensen, Karsten (Archaeological Textiles Review, 2024)
This study focuses on reliable methods for measuring the use of resources determining the extent or amount of skin used in Inuit garments. A collection of parkas of known provenance dating from approximately 1830 to 1940 CE currently housed at the National Museum of Denmark was measured using three quantitative metric methods: 3D-measurement with a FaroArm (Method 1), tape measurement (Method 2), and 2D-measurement of digital images (Method 3). Methods 1 and 3 produced statistically reliable results, while Method 2 failed. This research is a sub-study within a project that aims to reconnect Inuit garments that are currently only provisionally numbered with their original provenance information by applying measuring methods. The hypothesis supporting this study posits that three parameters: 1) design, 2) animal species, and 3) material resource usage, provide sufficient data to categorise unidentified items geographically and identify the gender for whom the garments were earmarked.